Avalanche Potential Analysis using Resistivity Method and USLE Method on Ranu Pani Area, Senduro Sub-district of Lumajang Regency - Siswo Purnomo; Sunaryo Sunaryo; Luchman Hakim (Natural B, Journal of Health and Environmental Sciences, 2012)
Has done research in the Ranu Pani area is one of the area where landslides have its potentiality, due to its location on the edge of the mountains where the soil is clay, slightly, sandy and has a very high fertility rates. One of the methods used to analyze landslide potential is using USLE (Universal Soil Loss Equation). In addition, the resistivity method with dipole-dipole configuration is also used to determine the structure of the soil and slip areas in the hills in the area Ranu Pani. Debris flow obtained from calculations using the USLE method in the second trajectory is equal to 796.5 tons/year, and the third trajectory is equal to 291.506 tons/year. According to the classification level of erosion, Ranu Pani area is an area with very dangerous level of erosion hazard, because the value of debris flow is more than 180 tons/year. With the high value of debris flow erosion, causing higher sedimentation of the lake, because the Ranu Pani lake accommodate most of the debris flow erosion of the hills around it.